Use of Pre- and Intensified Postprocedural Physiotherapy in Patients with Symptomatic Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement Study (the 4P-TAVR Study) - M. Weber; U. Klein; A. Weigert; W. Schiller; V. Bayley-Ezziddin; D. C. Wirtz; A. Welz; N. Werner; E. Grube; G. Nickenig; J.-M. Sinning; A. Ghanem (Journal of Interventional Cardiology)
Background. Physiotherapy prior to open-heart surgery lowers the rate of pneumonia and length of the hospital stay. Pneumonia is a major contributor to short-term mortality following transcatheter aortic valve replacement (TAVR). Hence, we hypothesized that pre- and intensified postprocedural physiotherapy in patients undergoing TAVR might impact the net functional and clinical outcome. Methods and Results. The 4P-TAVR study was a prospective, monocentric, randomized trial. The study was designed to compare the efficacy and safety of intensified periprocedural physiotherapy including inspiratory muscle training versus standard postprocedural physiotherapy. Patients were randomized in a 1 : 1 fashion. 108 patients were included and followed up for 90 days after TAVR. While patients in group A (control group: 50 patients, age: 81.7 ± 5.0 years, 52% male) did not receive physiotherapy prior to TAVR, group B (intervention group: 58 patients, age: 82.2 ± 5.82 years, 47% male) participated in intensive physiotherapy. Compared to the control group, patients in the interventional group showed a lower incidence of postinterventional pneumonia (10 [20.0%] vs. 3 [5.1%], p=0.016) and had a 3-day shorter mean hospital stay (13.5 ± 6.1 days vs. 10.1 ± 4.7 days, p=0.02). The primary composite endpoint of mortality and rehospitalization was not different between the groups. Conclusion. Intensified physiotherapy is safe and has positive effects on clinical outcomes up to 90 days after TAVR but has no impact on the primary combined endpoint of mortality and rehospitalization. Longer follow-up, a multicenter design, and a higher number of subjects are needed to confirm these preliminary results. This trial is registered with DRKS00017239.